Xpert MTB/RIF Ultra: Optimal procedures for the detection of Mycobacterium tuberculosis in cerebrospinal fluid. (February 2019) - Chin, Jerome H.; Ssengooba, Willy; Grossman, Scott; Pellinen, Jacob; Wadda, Vincent
Abstract: Tuberculosis is the leading infectious cause of death globally and extra-pulmonary disease occurs in 15% of incident cases annually. Tuberculous meningitis (TBM) is arguably the most lethal form of tuberculosis and requires prompt diagnosis and initiation of treatment to prevent death and serious neurological disability. The development of rapid diagnostic tests using polymerase chain reaction (PCR) technology for the detection of Mycobacterium tuberculosis (MTB), including the World Health Organization (WHO) – endorsed Xpert MTB/RIF Ultra assay, has allowed earlier definite diagnosis of TBM than conventional culture methods which usually take two weeks or longer for positive identification of MTB. Detection of MTB in cerebrospinal fluid (CSF) using PCR assays requires special attention to the collection, handling, and processing of CSF. Herein we present best practices guidance to maximize the detection rate of MTB in CSF using Xpert MTB/RIF Ultra.